Effect of Canopy Size of Acacia lIilotica on Rice (Oryza sativa L.) Productivity in a Traditional Agroforestry in the Central India - Pandey, C B; Sharma, D K (Annals of Arid Zone, 2016)
Influence of different canopy sizes (large, medium and small) of Acacia ni/otica on the growth and yield of rice crop was evaluated in a traditional agroforestry system in a dry tropical climate of India. Light intensity at ground level was lowest at 2 m from the tree trunk and increased with the distance. Maximum light was under the large tree canopy (62%) and minimum under the small tree canopy (44%). Soil organic C and total N were greater by 53% and 113%, respectively, under the large tree canopy, and 44% and 78%, respectively, under the small tree canopy compared to open field. Contrary to higher. organic C and total N, C/N ratio in the soil was lower'under all the canopy sizes. Crop density, above-ground/below-ground biomass ratio and grain yield under all the canopy sizes were lowest at 2 m from the tree trunk and increased with the distance. The crop density, yield and Ab/Bb ratio were reduced maximum 35, 30 and 15%, respectively, under the large tree canopy and minimum 17, 12 and 1.3%, respectively, under the small tree canopy. Harvest index declined under' the large tree canopy compared to open field. On the contrary, it increased under the small tree canopy, but grain yield declined.